Wear-resistant and corrosion-resistant steel for 690MPa-grade photovoltaic bracket and manufacturing method of wear-resistant and corrosion-resistant steel

By reasonably selecting and matching elements to form appropriate hard phase particles, the shortcomings of the steel for photovoltaic brackets in terms of wear resistance are solved, and high-strength, excellent wear-resistant and corrosion-resistant steel for photovoltaic brackets are achieved, which improves its service life and safety.

CN119663126AActive Publication Date: 2025-03-21ANGANG STEEL CO LTD

Patent Information

Application Number
CN202410857970.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-28
Publication Date
2025-03-21
Estimated Expiration
2044-06-28

AI Technical Summary

Technical Problem

The existing steel for photovoltaic brackets has shortcomings in wear resistance, and it is difficult to ensure durability and safety when used in windy and sandy areas.

Method used

Wear-resistant and corrosion-resistant steel for 690MPa grade photovoltaic brackets are used, and its chemical compositions include C, Si, Mn, P, S, Cr, Cu, Sb, Ti, Mo, Ce and Al. By reasonably matching these elements and their content, appropriate hard phase particles are formed, which improves the hardness and wear resistance of the steel, and at the same time enhances its atmospheric corrosion resistance.

Benefits of technology

The production of thin-spec and high-strength photovoltaic bracket steel has been achieved, and it has excellent wear resistance and atmospheric corrosion resistance. It overcomes the problem of insufficient wear resistance in the existing technology and improves the service life and safety of the photovoltaic bracket.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004918544380000071
    Figure BDA0004918544380000071
  • Figure BDA0004918544380000081
    Figure BDA0004918544380000081
  • Figure BDA0004918544380000082
    Figure BDA0004918544380000082
Patent Text Reader

Abstract

The steel comprises the following chemical components in percentage by weight: 0.083 to 0.103 percent of C, 0.41 to 0.59 percent of Si, 0.98 to 1.19 percent of Mn, 0.092 to 0.106 percent of P, less than or equal to 0.006 percent of S, 0.62 to 0.86 percent of Cr, 0.18 to 0.26 percent of Cu, 0.098 to 0.117 percent of Sb, 0.048 to 0.063 percent of Ti, 0.23 to 0.35 percent of Mo, 0.0144 to 0.0164 percent of Ce and 0.048 to 0.068 percent of Als, wherein P / Ce is 6.3 to 6.5 percent, and Si / Mo is 1.1 to 2.6 percent. The manufacturing method comprises the steps of smelting, slab continuous casting, casting blank heating, rolling, laminar cooling and coiling. The Rel of the steel ranges from 721 MPa to 733 MPa, the Rm of the steel ranges from 788 MPa to 808 MPa, and A of the steel is larger than 29%; the surface hardness of the steel ranges from 234 HBW to 241 HBW, the wear rate relative to Q345B ranges from 26.4% to 27.1%, the corrosion rate relative to Q345B ranges from 28.62% to 30.83%, and the problem that in the prior art, wear resistance is not achieved is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of corrosion-resistant steel for photovoltaic brackets and relates to a 690MPa-grade wear-resistant and corrosion-resistant steel for photovoltaic brackets and a manufacturing method thereof. Background Art

[0002] Photovoltaic brackets are important supporting devices in photovoltaic power generation systems, and their performance directly affects the service life of photovoltaic power stations. Since photovoltaic brackets are exposed to the atmosphere for a long time, they must withstand the erosion of external environments such as moisture, light, and temperature, especially in some desert areas with strong winds and sand, and they must also withstand the abrasion of wind and sand, which affects the safety and durability of the brackets. Therefore, the corrosion resistance and wear resistance of the material are factors that must be considered.

[0003] At present, the main materials used to manufacture photovoltaic brackets are aluminum alloy, hot-dip galvanized steel and weathering steel. Among them, aluminum alloy brackets are relatively expensive and have low bearing capacity, and have no competitive advantage; the production process of hot-dip galvanized steel is complicated and the galvanizing process has serious environmental pollution; and weathering steel is an ideal material for processing photovoltaic brackets due to its own corrosion resistance. However, the weathering steel used in the domestic production of photovoltaic brackets often only considers its atmospheric corrosion resistance and ignores the wear resistance required for the bracket to be in service. At the same time, with the development of the photovoltaic industry, thin-gauge, high-strength photovoltaic bracket steel has become the selected trend. Therefore, it is urgent to develop a thin-gauge, high-strength photovoltaic bracket steel with excellent wear resistance and atmospheric corrosion resistance.

[0004] Prior to the present invention,

[0005] The publication number of CN 115896613 A is "a kind of high-strength and low-cost weathering steel for photovoltaic brackets and its preparation method and application". The composition is: C: ≤0.10%, Si: 0.02%~0.50%, Mn: 0.80%~2.00%, P≤0.030%, S≤0.005%, Cr: 0.20%~0.80%, Cu: 0.20%~0.60%, W: 0.05%~0.50%, Als: 0.010%~0.050%, and the balance is Fe and inevitable impurities. The precious metal W is added to the invention, and the addition of W to the steel is bound to increase the alloy cost. In addition, the invention also uses a tempering process to improve the mechanical properties of the steel, which not only prolongs the production cycle, but also increases the production cost. Moreover, the invention steel describes the influence of elements on atmospheric corrosion resistance, and does not study the wear resistance of steel for photovoltaic brackets.

[0006] The "A low-cost 800MPa-level titanium-containing weathering steel for photovoltaic brackets and its preparation method" with publication number CN116179961A has the following components: C: ≤0.08%, Si: 0.35%-0.50%, Mn: 0.40%-0.60%, P: 0.08%-0.12%, S: ≤0.010%, Cu: 0.25%-0.45%, Cr: 0.75%-1.00%, Ti: 0.120%-0.170%, N≤0.0040%, and the rest is Fe and impurities. The high content of Cu in this invention not only increases the production cost, but also easily causes "copper brittleness" defects on the edge of the steel plate without other process control; the corrosion resistance of this invention steel is only evaluated by the atmospheric corrosion resistance index I, which is calculated based on a theoretical formula and has not been verified by corrosion tests. The actual corrosion resistance of this invention steel is unknown. And the specific influence on wear resistance is not mentioned in the invention.

[0007] The publication number CN109402508B states that “a low-carbon microalloyed Q690 grade high-strength weathering steel and its preparation method” has a composition of: C: 0.03% to 0.10%, Si: 0.10% to 0.50%, Mn: 1.20% to 2.00%, S: 0.002% to 0.010%, P: 0.003% to 0.015%, Al: 0.01% to 0.05%, V: 0.05% to 0.15%, N: 0.01% to 0.02%, Cr: 0.30% to 0.80%, Ni: 0.30% to 0.80%, Cu: 0.15% to 0.55%, Mo: 0.15% to 0.55%, and the balance is Fe and impurities. The invention uses VN-Cr microalloying technology to improve the toughness of the material, and improves the corrosion resistance of the material by adding Cu-Ni elements, but V, Cu, and Ni are all precious metal elements and the amount added in the invention is relatively large, which greatly increases the production cost. In addition, the invention does not mention the specific impact on wear resistance, and the corrosion resistance is only predicted by the theoretical parameter I, and the specific corrosion resistance index of the invented steel is not explained, so its actual wear resistance and corrosion resistance effect are unknown.

[0008] The "700MPa wear-resistant and corrosion-resistant steel and its manufacturing method" with publication number CN114737116B has the following components: C: 0.069% to 0.090%, Si: 0.65% to 0.93%, Mn: 1.18% to 1.59%, P≤0.018%, S≤0.006%, Cr: 0.91% to 1.48%, Cu: 0.14% to 0.24%, Sb: 0.055% to 0.091%, W: 0.45% to 0.65%, Ti: 0.071% to 0.096%, Als: 0.015% to 0.045%, N≤0.004%, and the balance is Fe and impurities. The invention improves the wear resistance of the material through the synergistic effect of Si, Mn, Cr and W elements, and forms a certain amount of FeMnCrC, TiC and WC. However, the invented steel is mainly suitable for the manufacture of container steel, and does not have high requirements on the plasticity and forming performance of the material, and is not applicable to the plasticity requirements of photovoltaic brackets during forming. Summary of the invention

[0009] The purpose of the present invention is to provide a 690MPa grade wear-resistant and corrosion-resistant steel for photovoltaic brackets and a manufacturing method thereof. The photovoltaic bracket steel is a thin-gauge, high-strength steel with excellent wear resistance and atmospheric corrosion resistance, solving the problem that the prior art does not have wear resistance.

[0010] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0011] The present invention provides a 690MPa-level wear-resistant and corrosion-resistant steel for a photovoltaic bracket, wherein the chemical composition is C: 0.083%-0.103%, Si: 0.41%-0.59%, Mn: 0.98%-1.19%, P: 0.092%-0.106%, S: ≤0.006%, Cr: 0.62%-0.86%, Cu: 0.18%-0.26%, Sb: 0.098%-0.117%, Ti: 0.048%-0.063%, Mo: 0.23%-0.35%, Ce: 0.0144%-0.0164%, Als: 0.048%-0.068%, wherein P / Ce is controlled at 6.3-6.5, Si / Mo is controlled at 1.1-2.6, and the remainder is Fe and unavoidable impurities.

[0012] The present invention selects the above alloy element types and contents because:

[0013] C: As one of the key elements to ensure the strength and hardness of the material. In the present invention, C mainly improves the strength of the steel plate by solid solution strengthening and precipitation strengthening. When added in conjunction with Mo, a hard phase Mo2C3 can be generated inside the grains to improve the hardness and wear resistance of the steel. However, excessive C will deteriorate the plasticity and forming properties of the steel plate. In the present invention, the content of C is limited to 0.083% to 0.103%.

[0014] Si: As one of the important elements for improving corrosion resistance, strength and hardness. Si is easy to be enriched on the surface of the steel plate, thereby forming a dense SiO2 oxide protective film on the surface of the product that is tightly bonded to the matrix, which can effectively inhibit the penetration of corrosive media. When added in combination with Mo, it can form Mo2Si3 hard phase particles with free Mo in the steel. By controlling the final rolling temperature and the coiling temperature, it is easy to disperse and precipitate micron-level (40-70μm) hard phase Mo2Si3 particles near the grain boundary or inside the grain, which can effectively improve the hardness and wear resistance of the steel. However, too high Si content will not only have an adverse effect on the surface quality, but also deteriorate the performance of the steel due to the generation of large-sized Mo2Si3 particles. Therefore, the content of Si in the present invention is limited to 0.41% to 0.59%. In addition, the content of Si and Mo determines the type of Si-Mo and the state of the precipitated particles. In order to obtain more dispersed precipitated phase particles, the ratio of Si / Mo is controlled to be 1.1 to 2.6.

[0015] Mn: One of the main strengthening elements in steel, it can improve the strength of steel plate through solid solution strengthening. At the same time, Mn in the present invention, as an important austenitizing stabilizing element, can expand the austenite phase region, has the effect of improving the stability of the retained austenite in the steel, and can improve the plasticity of the material. Therefore, in order to ensure and improve the strength and plasticity of the material, the content of Mn in the present invention is set to 0.98% to 1.19%.

[0016] P: It is mainly used as one of the elements that significantly improve the strength and corrosion resistance of materials. However, when the content of this element is too high, it is easy to segregate at the grain boundary, which will not only reduce the plasticity and toughness of the material, but also affect the corrosion resistance of the material. Therefore, in the present invention, it is added in combination with the rare earth element Ce. The solid-dissolved rare earth element can refine the dendrites, increase the equiaxed crystal ratio, and then inhibit the segregation behavior of P, and can also significantly improve the corrosion resistance of the material. In order to make the corrosion resistance effect significant in the present invention, the P content is set to 0.092% to 0.106%. In order to reduce the segregation of the P element in the ingot, the P / Ce value is limited to 6.3 to 6.5.

[0017] S: It is a harmful impurity element in steel, which is easy to form defects such as segregation and inclusion, and will deteriorate the impact toughness and hot working performance of the steel plate. However, if the S content is controlled too low, the smelting cost will increase. Therefore, in the present invention, the S content should be controlled below 0.006%.

[0018] Cr: Mainly improves the strength of steel by solid solution strengthening. At the same time, this element is the main corrosion-resistant element and is often enriched in the rust layer. It is not only easy to form a dense oxide film on the surface of the steel plate, but also forms a dense Cr-Cu compound protective rust layer with the Cu element on the surface of the substrate, which can significantly inhibit the penetration of corrosive media, thereby achieving a double-layer corrosion resistance effect, and can replace part of the corrosion resistance of Cu. However, when its content is too high, it will not only deteriorate the welding performance of the steel plate but also increase the difficulty of smelting. Therefore, the Cr content in the present invention is controlled to be 0.62% to 0.86%.

[0019] Cu: One of the important corrosion-resistant elements. This element is often enriched in the rust layer, which can effectively improve the permeability of the corrosive medium, and it is easy to form a dense Cu-P compound protective rust layer with the P element on the surface of the substrate, which can further inhibit the penetration of the corrosive medium. At the same time, this element is often dissolved in Fe to form a substitutional solid solution, which has a solid solution strengthening effect, thereby improving the strength of the steel plate. However, when the Cu content is too high, it not only increases the cost, but also easily causes the edge of the steel plate to produce "copper brittleness" defects in the absence of Ni elements. Therefore, in the present invention, the rare earth Ce element is added to make it dispersed and combined with a heating process to avoid the occurrence of "copper brittleness" defects. The present invention limits its content range to 0.18% to 0.26%.

[0020] Ti: A strong C and N compound-forming element, an important element for improving strength. During the heating process of the steel plate, it often forms Ti-N compounds with N to inhibit the growth of austenite grains and achieve the purpose of grain refinement; it forms fine carbides and nitrides or carbonitrides with C and N, and then precipitates fine compounds during the cooling and coiling of the steel plate, playing a precipitation strengthening role. The present invention limits its range to 0.048% to 0.063%.

[0021] Sb: An effective element for improving the corrosion resistance and wear resistance of steel plates. This element easily forms a dense oxide film on the surface of the substrate, improving the passivation ability of the steel plate. By adding it in combination with P, Cu, and Cr, it is synergistically enriched in the rust layer, forming a dense Sb-P-Cu-Cr composite protective rust layer that is tightly bonded to the substrate, which can further hinder the invasion of corrosive media. In addition, the Sb3O4 hard phase formed by this element inside the substrate precipitates along the grain boundaries during cooling and coiling, which can further improve the wear resistance of the steel plate. The Sb content in the present invention is controlled to be 0.098% to 0.117%.

[0022] Mo: There are three main forms of existence in steel. One part is dissolved in iron to form a substitutional solid solution, which improves the yield strength of the steel; one part forms a Mo-C hard phase Mo2C3 with the free C in the steel, which can significantly improve the hardness and wear resistance of the steel; and a small part is segregated at the grain boundary; when Mo is added in combination with the rare earth Ce, the strong affinity of Ce can reduce the segregation of Mo at the grain boundary. Ce promotes the uniform precipitation of the Mo2C3 hard phase and inhibits its aggregation and growth, which can further improve the wear resistance of the steel plate; especially when added in combination with Si, it can form Mo2Si3 hard phase particles with the free Si in the steel. By controlling the final rolling temperature and the coiling temperature, micron-level (40-70μm) hard phase Mo2Si3 particles will be dispersed and precipitated near the grain boundary or inside the grain, which greatly improves the hardness and wear resistance of the steel. In order to better exert the synergistic wear-resistant effect of Si and Mo, the present invention limits Si / Mo to 1.1-2.6. However, when the Mo content is too high, its segregation degree at the grain boundary will increase, and the plasticity, toughness and welding performance of the steel will be deteriorated. The Mo content of the present invention is controlled at 0.23%-0.35%.

[0023] Als: An important deoxidizing element that can purify the molten steel into a low-oxygen environment so that the rare earth will not react with the excessive oxygen in the molten steel after being added, and the solid solution effect of the rare earth can be fully exerted. A large part of the role of this element is to be added in conjunction with the addition of rare earth. The present invention limits its range to 0.048% to 0.068%.

[0024] Ce: (1) As an effective deoxidizing and desulfurizing element, it can purify the molten steel and improve the mechanical properties of the product; it can change the shape and type of inclusions, reduce the potential difference between the inclusions and the matrix, reduce the tendency of electrochemical corrosion caused by inclusions, and effectively improve the corrosion resistance of the steel plate; (2) It has the function of dispersing Cu, which can avoid the occurrence of "copper brittleness" defects on the one hand, and improve the utilization rate of Cu on the other hand, thereby increasing the ratio of the protective phase α-FeOOH / γ-FeOOH, improving the stability of the rust layer, and further improving the corrosion resistance of the steel plate; (3) The addition of Ce can effectively inhibit P segregation, thereby improving the plasticity of the material, especially in the case of high P in the present invention. In order to make the corrosion resistance effect significant and inhibit P segregation in the present invention, the P / Ce value is limited to 6.3-6.5; (4) Improve the segregation of Mo, promote the uniform precipitation of the hard phases Mo2C3 and Mo2Si3, and inhibit the aggregation and growth of the phases, thereby improving the wear resistance of the steel plate. The present invention limits the range to 0.0144% to 0.0164%.

[0025] The present invention also provides a method for manufacturing wear-resistant and corrosion-resistant steel for 690MPa-level photovoltaic brackets. The method obtains wear-resistant and atmospheric corrosion-resistant steel containing the above-mentioned chemical components through pre-desulfurization of molten iron, top and bottom blowing of converter, LF refining outside the furnace, slab continuous casting, ingot heating, hot rolling, laminar cooling and coiling, and specifically includes the following contents.

[0026] Smelting: firstly, the molten iron is subjected to a desulfurization pretreatment so that the S in the molten iron after desulfurization is ≤0.002%. A top and bottom composite blowing process is adopted, and the converter tapping temperature is 1651-1666°C. Then, the molten iron is fed into the LF furnace for heating and component fine-tuning, and then Si-Ca wire feeding treatment is carried out to further reduce the O and S contents, and ensure that the free O content in the steel should be controlled below 3.8ppm; 7-9 minutes before the end of the vacuum treatment in the LF furnace, 20% Ce-Fe rare earth alloy 1.60-1.82kg / ton of steel is added to the LF furnace, and then argon weak blowing (argon flow rate 108-128NL / min, pressure 0.16-0.29MPa) is carried out, and stirring is carried out. The weak blowing time is 3.9-5.9min to ensure that the inclusions are fully floated and denatured.

[0027] Slab continuous casting: During the slab continuous casting, protective slag is used throughout the process to protect the molten steel to prevent the molten steel from being exposed to the air. The thickness specification of the continuous casting billet is 210-230mm. Since the rare earth element Ce in the invention steel has a strong affinity, it is easy to form a large number of rare earth inclusions with the O and S elements in the steel, affecting the fluidity of the molten steel. Therefore, the pulling speed is controlled to 1.28-1.48m / min during casting; and in the present invention, the P element content is relatively high, and P segregation is very likely to occur, thereby reducing the plastic toughness of the material. Therefore, in order to reduce the center segregation of the continuous casting billet, the superheat is controlled between 10-13°C during casting, and electromagnetic stirring technology is used at the same time, wherein the electromagnetic stirring current is 364-368A, 5-7HZ.

[0028] Ingot heating: One of the main ways to improve the strength of the steel plate in the present invention is microalloy solid solution strengthening, especially when Si and Mo elements are added in combination. In order to ensure that Si, Mo and other alloy elements are fully dissolved, the ingot is heated to 1272-1298°C. The steel of the present invention is copper-containing steel. Usually, Cu and Ni elements should be added in combination to suppress the occurrence of "copper brittleness" defects. However, in order to reduce costs, the present invention does not add precious metal Ni, but avoids the occurrence of "copper brittleness" defects of copper-containing steel by formulating a reasonable heating process. Therefore, in order to avoid the occurrence of "copper brittleness" defects caused by the precipitation of low-melting-point element Cu on the surface of the steel plate, the atmosphere of the heating furnace is set to a reducing atmosphere with an air-fuel ratio between 1.6 and 2.0. When the heating temperature is below 1105°C, slow heating is required, and the heating rate is controlled at 6.6 to 8.7°C / min to ensure uniform temperature inside and outside the billet; when the temperature is above 1105°C, rapid heating is required, and the heating rate is controlled at 16.9 to 18.9°C / min; since the longer the heating time, the more conducive it is for Cu to diffuse along the austenite grain boundary, and the more likely it is to produce "copper brittleness" defects, the furnace time is controlled to be ≤210min, preferably 184 to 207min, with the soaking section holding time being 36 to 51min.

[0029] Rolling: Rough rolling and finishing rolling are two-stage temperature-controlled rolling. Rough rolling adopts high temperature and large reduction. The final rolling temperature of rough rolling is 1109-1141℃, and the cumulative reduction rate of rough rolling stage is 82.3%-85.5%. The higher cumulative reduction can not only press the defects in the ingot, but also form more dislocations by increasing deformation, thereby improving the strength of the material by dislocation strengthening. The start rolling temperature of finishing rolling is 1091℃-1119℃. In order to eliminate the adverse effects of dislocation strengthening on plasticity in the rough rolling stage and ensure that the hard phases of Mo2C3 and Mo2Si3 are fully precipitated, a higher final rolling temperature is set for this purpose, and the final rolling temperature of finishing rolling is set to 938-954℃; in order to ensure the straightness and precision of the finished steel plate, the reduction rate of the last rolling of finishing rolling is controlled at 15.2%-16.1%. And during the rolling process, the rolling convexity target is controlled at 34-41μm.

[0030] After finishing rolling, laminar cooling is performed in two stages. In the first stage, the steel is cooled to 739-759 (this temperature range belongs to the ferrite transformation range) at a cooling rate of 21-28°C / s, and air-cooled for 8-10s. In this stage, sufficient soft ferrite structure can be obtained and Mo2C3 and Mo2Si3 phases can be inoculated so that they are easy to precipitate and grow, so as to ensure the plasticity and wear resistance of the steel plate; then the second stage is cooled at a cooling rate of 33-44°C / s, and the steel is coiled at 587-607°C. In this stage, sufficient hard bainite can be generated to ensure the strength performance of the product. And this coiling temperature has a good effect on refining grains and inhibiting the coarsening of Mo2C3 and Mo2Si3 precipitation phases.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] Through precise control of the composition and organizational proportion, the yield strength of the wear-resistant and corrosion-resistant steel coil for photovoltaic brackets with a thickness of 1.5 to 4.0 mm produced by the above chemical composition and rolling process is greater than 690 MPa, the tensile strength is greater than 780 MPa, the elongation is greater than 29%, the cold bending performance is qualified, and the plasticity is excellent; through the control of the hard phase precipitates and their sizes, the surface hardness of the invented steel is 234 to 241 HBW, and the wear rate relative to Q345B is 26.4% to 27.1%; through the reasonable matching of corrosion-resistant elements, in the rapid corrosion evaluation test simulating the C4 grade atmospheric environment, the corrosion rate of the invented steel relative to Q345B is 28.62% to 30.83%. The present invention overcomes the shortcomings of the prior art, and makes the manufacturing process of the wear-resistant and corrosion-resistant steel plate for photovoltaic brackets with thin specifications and high strength simple, and not only has strong plasticity, but also has excellent wear resistance and atmospheric corrosion resistance. This ensures that the photovoltaic bracket will not have defects such as cracks during the bending process and will be safe and durable when used in windy and sandy areas. DETAILED DESCRIPTION

[0033] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. The described embodiments are only a part of the embodiments of the present invention, not all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] The present invention is described in more detail below through examples.

[0035] The composition of the steel of the embodiment of the present invention is shown in Table 1, the main process parameters of smelting and continuous casting of the steel of the embodiment of the present invention are shown in Table 2, the heating process parameters of the steel of the embodiment of the present invention are shown in Table 3, the rolling and coiling process parameters of the steel of the embodiment of the present invention are shown in Table 4, the various properties of the steel of the embodiment of the present invention are shown in Table 5, the microstructure of the steel of the embodiment of the present invention is shown in Table 6, and the results of the immersion corrosion test of the steel of the embodiment of the present invention are shown in Table 7.

[0036] Table 1 Composition of steel according to the present invention (wt%)

[0037]

[0038] Table 2 Main process parameters of steel smelting and continuous casting in the embodiment of the present invention

[0039]

[0040] Table 3 Main process parameters for heating of steel according to the present invention

[0041] Example Heating temperature / ℃ Air-fuel ratio Slow heating rate / ℃ / min Rapid heating rate / ℃ / min Total heating time / t Heat preservation time / t 1 1272 1.6 6.6 16.9 184 36 2 1275 1.6 6.8 17.2 187 38 3 1279 1.7 7.1 17.5 190 40 4 1282 1.7 7.4 17.8 193 42 5 1286 1.8 7.7 18.1 196 44 6 1290 1.9 8.0 18.4 199 46 7 1294 2.0 8.3 18.7 203 48 8 1298 2.0 8.7 18.9 207 51

[0042] Table 4 Main process parameters of rolling and cooling of steel in the embodiment of the present invention

[0043]

[0044] Table 5 Test results of various performance indicators of the embodiment

[0045]

[0046] Table 6 Microstructure of steel according to the present invention

[0047]

[0048] It can be seen from Table 5 that the yield strength of the example steels of the present invention is 721-733 MPa, all reaching the design strength of 690 MPa or above, the tensile strength is between 788-808 MPa, the elongation is greater than 29%, and the cold bending performance is qualified, indicating that the strength of the example steels not only meets the design requirements, but also has high plasticity; the hardness value of the example steels is between 234-241 HBW.

[0049] The wear resistance test in Table 5 was conducted on a wet rubber wheel abrasive wear tester. The sample size was 57.0mm×25.5mm×6.0mm. The wear test was conducted in accordance with "JB / T 7705-1995 Loose Abrasive Wear Test Method Rubber Wheel Method". The test results show that the wear rate of the example steel relative to Q345B is between 26.4% and 27.1%, which shows that the example steel has higher wear resistance.

[0050] The results in Table 6 show that the structure of the invented steel is composed of ferrite + bainite + a small amount of pearlite, the structure is uniform and fine, and fine Mo2Si3 hard phase is precipitated in the structure, among which Mo2Si3 with a size range of 40 to 70 um accounts for 87.6 to 89.7%. This level of precipitated phase is beneficial to improving the wear resistance of the invented steel.

[0051] In order to simulate the corrosion situation in the C4 grade atmospheric environment, the invention steel was subjected to a 72-hour periodic immersion rapid corrosion evaluation test according to the test method specified in TB / T 2375-1993. Table 7 shows the corrosion resistance comparison results of the embodiment steel of the invention and the comparative steel. It can be seen from Table 7 that the corrosion resistance of the embodiment steel of the invention is significantly better than that of the comparative steel Q345B.

[0052] Table 7 Comparison results of rapid corrosion test of steel according to the present invention and comparative steel

[0053]

[0054] It is to be noted that the above embodiments are only for illustrating the technical concept and features of the present invention, and are not intended to limit the present invention. Any equivalent replacement or modification that does not deviate from the essence of the present invention shall fall within the protection scope of the present invention.

Claims

1. A 690MPa grade wear-resistant and corrosion-resistant steel for photovoltaic support and a manufacturing method thereof, characterized in that: The chemical composition of the steel is as follows by weight: C: 0.083% ~ 0.103%, Si: 0.41% ~ 0.59%, Mn: 0.98% ~ 1.19%, P: 0.092% ~ 0.106%, S: ≤ 0.006%, Cr: 0.62% ~ 0.86%, Cu: 0.18% ~ 0.26%, Sb: 0.098% ~ 0.117%, Ti: 0.048% ~ 0.063%, Mo: 0.23% ~ 0.35%, Ce: 0.0144% ~ 0.0164%, Als: 0.048% ~ 0.068%, wherein P / Ce is controlled at 6.3 ~ 6.5, Si / Mo is controlled at 1.1 ~ 2.6, and the balance is Fe and unavoidable impurities.

2. The 690MPa wear-resistant and corrosion-resistant steel for photovoltaic bracket according to claim 1 is characterized in that: The metallographic structure of the steel is ferrite + bainite + a small amount of pearlite, with the proportion of ferrite being 26.9% to 28.7%, the proportion of bainite being 65.2% to 66.3%, and the ferrite grain size being ≥ 10.5; fine Mo2Si3 hard phase is precipitated in the structure, of which the proportion of Mo2Si3 with a size range of 40 to 70 μm is 87.6% to 89.7%.

3. The 690MPa wear-resistant and corrosion-resistant steel for photovoltaic support according to claim 1, characterized in that: The yield strength of the steel is between 721 and 733 MPa, the tensile strength is between 788 and 808 MPa, and the elongation is greater than 29%; the surface hardness of the steel is 234 to 241 HBW, and the wear rate relative to Q345B is 26.4% to 27.1%.

4. The 690MPa wear-resistant and corrosion-resistant steel for photovoltaic support according to claim 1, characterized in that: In the rapid corrosion evaluation test simulating the C4 grade atmospheric environment, the corrosion rate of steel was 0.959~1.033g / m 2 .h, the corrosion rate relative to Q345B is 28.62%~30.83%.

5. The 690MPa wear-resistant and corrosion-resistant steel for photovoltaic support according to claim 1, characterized in that: The thickness of the steel plate is 1.5 to 4.0 mm.

6. A method for manufacturing the 690MPa wear-resistant and corrosion-resistant steel for photovoltaic brackets according to any one of claims 1 to 5, comprising smelting, slab continuous casting, billet heating, rolling, laminar cooling and coiling, characterized in that: The ingot is heated to 1272-1298°C, the air-fuel ratio is between 1.6 and 2.0, the heating rate is controlled at 6.6-8.7°C / min when the heating temperature is below 1105°C; the heating rate is controlled at 16.9-18.9°C / min when the temperature is above 1105°C; the furnace time is controlled to be ≤210min; the rolling adopts two-stage controlled rolling of rough rolling and finishing rolling, the final rolling temperature of rough rolling is 1109-1141°C, the cumulative reduction rate in the rough rolling stage is 82.3%-85.5%; finishing rolling The starting rolling temperature is 1091℃~1119℃, the finishing rolling temperature is 938~954℃, the reduction rate of the last finishing rolling is controlled at 15.2%~16.1%, and the rolling convexity target is controlled at 34~41μm; after finishing rolling, two-stage laminar cooling is adopted. In the first stage, the steel is cooled to 739~759℃ at a cooling rate of 21~28℃ / s, air cooled for 8~10s, and then cooled to 587~607℃ for coiling at a cooling rate of 33~44℃ / s in the second stage.

7. The method for manufacturing 690MPa grade wear-resistant and corrosion-resistant steel for photovoltaic support according to claim 6, characterized in that: During smelting, the molten iron is first subjected to desulfurization pretreatment. After desulfurization, the S in the molten iron is ≤0.002%. A top and bottom composite blowing process is adopted, and the converter tapping temperature is 1651-1666°C. After that, Si-Ca wire feeding treatment is carried out to control the free O content in the steel below 3.8ppm. 20% Ce-Fe rare earth alloy 1.60-1.82kg / ton of steel is added to the LF furnace 7-9min before the end of the vacuum treatment in the LF furnace, and then argon weak blowing is carried out.

8. The method for manufacturing 690MPa-grade wear-resistant and corrosion-resistant steel for photovoltaic brackets according to claim 7, characterized in that: The flow rate of argon weak blowing is 108-128NL / min, the pressure is 0.16-0.29MPaa, and the weak blowing time is 3.9-5.9min.

9. The method for manufacturing 690MPa wear-resistant and corrosion-resistant steel for photovoltaic support according to claim 6, characterized in that: The ingot heating time in the furnace is 184 to 207 minutes, of which the soaking time is 36 to 51 minutes.

Citation Information

Patent Citations

  • A low-carbon microalloyed Q690 grade high-strength weathering steel and its preparation method

    CN109402508B

  • A 700MPa grade wear-resistant and corrosion-resistant steel and its manufacturing method

    CN114737116B

  • Weathering resistant steel for high-strength low-cost photovoltaic support and preparation method and application of weathering resistant steel

    CN115896613A

  • Low-cost titanium-containing weathering steel for 800 MPa-grade photovoltaic support and preparation method of low-cost titanium-containing weathering steel

    CN116179961A

  • Coal-water abrasion and corrosion resistant steel plate for railway coal transport vehicle and manufacturing method thereof

    CN107653423A

Cited By

  • High-corrosion-resistance wear-resistant steel for railway wagon and manufacturing method of high-corrosion-resistance wear-resistant steel

    CN120138507A